Ernest MacMillan and England - Beckwith, John (Canadian University Music Review / Revue de musique des universités canadiennes, 1998)
The Canadian composer-conductor Ernest MacMillan wrote England, an Ode, for chorus and orchestra, in a German prison camp in World War I, and was awarded a D.Mus. by Oxford University for it, in absentia. The score is examined alongside background documents, including MacMillan's unpublished memoirs, for its ambitious musical features, its conformity to the degree specifications, and the influences it suggests (MacMillan studied works by Debussy and Skryabin while incarcerated, and received advice from a fellow-prisoner, the composer Benjamin Dale). The choice of text, a decidedly imperialistic poem by A. C. Swinburne, is measured against MacMillan's later association with Canadian cultural nationalism.